An assessment of the teacher-adviser's functions in the guidance program of Luis Palad Provincial High School - Jacela, Prosefina Abuel 1944-
This study sought to assess the functions of the teacher-advisers as guidance workers. This study also endeavored to determine the factors that may affect the teacher-advisers' performance in their guidance functions. The opinion survey method was used with the Personality Orientatioon Inventory and a questionnaire devised by the researcher. The findings of the study revealed that the teacher-advisers, based on the Personality Orientation Inventory, are time competent and other-oriented. Both teacher-advisers and students ranked homeroom and orientation as the most attended to among the guidance functions. Teacher-advisers ranked informal counseling as the least attended to among their guidance functions while students ranked parental contact last.